Pengaruh Penghindaran Pajak, Risiko Pajak, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Laia, Hilda Efri; Sicillia, Mita (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the effect of tax avoidance, tax risk, and firm size on firm value in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange during 2019–2023. Firm value reflects investors’ perceptions of performance, credibility, and long-term sustainability, while corporate tax behavior has increasingly attracted stakeholder attention due to its potential impact on market confidence and valuation. The population comprised 125 Consumer Non-Cyclicals companies listed on the exchange. Using purposive sampling based on predetermined criteria, 11 companies were selected, generating 55 observations over five years. The study used secondary data obtained from annual financial reports published on the official exchange website and company websites. Panel data regression analysis was employed, and model selection tests indicated that the Random Effect Model was the most appropriate specification. Data processing and statistical analysis were conducted using EViews 12.The results show that tax avoidance, tax risk, and firm size simultaneously have a significant effect on firm value. Partially, tax avoidance and firm size have positive and significant effects, whereas tax risk has a negative and significant effect on firm value. These findings indicate that effective tax management and firm characteristics play an important role in enhancing firm value and provide useful insights for management, investors, and policymakers in making informed economic and strategic decisions within relevant corporate governance and taxation contexts.